Cd1−xMgxS CQD thin films for high performance and highly selective NIR photodetection. Issue 36 (20th August 2021) - Kalsi, Tania; Kumar, Pragati
Abstract : Highly selective prototype NIR PDs are developed using Cd1− x Mg x S CQDs thin films. Besides simple and cost-effective fabrication, these PDs demonstrate high FOMs like fast response (∼110 ms) with a maximum specific detectivity of ∼3.45 × 10 13 Jones. Abstract : Development of high-performance and highly selective NIR photodetectors (PDs) using wide band gap semiconductors is a significant field of research in the present scenario. Herein, cost effective and easy fabrication of NIR PDs is demonstrated by employing the thin films of Cd1− x Mg x S ( x = 0, 0.01, 0.02, 0.03, 0.04 and 0.05) colloidal quantum dots (CQDs). The influence of doping on the transport behaviour of Cd1− x Mg x S CQD films was investigated by device performance under laser light illumination at various wavelengths ranging from 405 nm to 782 nm. An improvement in the photoresponsivity of the material (CdS) beyond its intrinsic absorption spectral range due to the incorporation of the dopant is noticed. In spite of the cost effective and easy fabrication process without the requirement of any rigorous synthesis procedure, the devices presented here demonstrate competitive figures of merit to those that are designed with complex structures and tedious procedures. The performance parameters viz response time, responsivity, photosensitivity, quantum efficiency, and specific detectivity were improved as a consequence of Mg doping and attained a maximum value of 110 ms, ∼26.9 A W −1, ∼4.7 × 10 4 %, ∼41.23% and ∼3.45 × 10 13 Jones, respectively. Besides, the sensing range of the PDs can be tuned from visible (650 nm) to NIR (782 nm) with a huge improvement in selectivity by incorporation of Mg.